2017
DOI: 10.1177/1040638717709856
|View full text |Cite
|
Sign up to set email alerts
|

Systemic necrotizing polyarteritis in three weaned lambs from one flock

Abstract: Systemic necrotizing polyarteritis was diagnosed in three 7-11-mo-old lambs from the same flock. Aneurysmal dilation and rupture of the gastroduodenal artery in 1 lamb resulted in fatal hemorrhage. All lambs had severe necrotizing vasculitis involving the small intestine, abomasum, mesentery, kidney, and heart with concurrent lymphocytic enteritis. Immunohistochemistry for T- and B-lymphocytes and macrophages found a T-cell- and macrophage-dominant transmural vascular infiltrate and T-cell-associated enteritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Systemic necrotizing vasculitis is a rare, sporadic disease recognized in individuals or clusters of sheep. 9,11,20,22,26 The histologic lesions have been considered typical of "polyarteritis nodosa" (PAN), which also has been reported in pigs, 15 cats, 5 dogs, 23 rats, 21 and humans. 7,10 Many veterinary reports use a definition of PAN derived from human studies, which is a necrotizing arteritis of medium or small arteries without vasculitis in arterioles, capillaries, or venules.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic necrotizing vasculitis is a rare, sporadic disease recognized in individuals or clusters of sheep. 9,11,20,22,26 The histologic lesions have been considered typical of "polyarteritis nodosa" (PAN), which also has been reported in pigs, 15 cats, 5 dogs, 23 rats, 21 and humans. 7,10 Many veterinary reports use a definition of PAN derived from human studies, which is a necrotizing arteritis of medium or small arteries without vasculitis in arterioles, capillaries, or venules.…”
mentioning
confidence: 99%
“…S1b) or previously performed (case Nos. 3-8), 8,26 demonstrated that transmural arterial infiltrates were predominantly lymphocytic (Suppl. Fig.…”
mentioning
confidence: 99%
“…In veterinary medicine, PAN is a common disease of laboratory animals, affecting mainly male rats (Lepherd et al, 2013). It has been described in blue foxes (Alopex lagopus) (Nordstoga and Westbye, 1976), cynomolgus macaques (Macaca fascicularis) (Albassam et al, 1993;Porter et al, 2003), sheep (Landsverk and Bratberg, 1979;Ferreras et al, 2013;Wessel et al, 2017;Pesavento et al, 2018), cattle (Filippich and Mudie, 1972), pigs (Hamir, 1980;Liu et al, 2005), dogs (Carpenter et al, 1988;Snyder et al, 1995) and cats (Altera and Bonasch, 1966;Campbell et al, 1972).…”
mentioning
confidence: 99%
“…A relationship with streptococcal infection has been suspected in pigs (Liu et al, 2005). However, no infectious agents have been detected in most cases of PAN in animals (Carpenter et al, 1988;Snyder et al, 1995;Porter et al, 2003;Wessel et al, 2017).…”
mentioning
confidence: 99%
“…SNP in sheep is an infrequently reported syndrome of unknown etiology, although several viruses, including BDV, BTV, EHDV, and OvHV-2, have been speculated. 13 A 2017 published report on a case of SNP in sheep clearly demonstrates how difficult it is to confirm a diagnosis associated with such lesions, 18 reinforcing the need to rely on other parameters such as agent identification to establish a definitive diagnosis. Confirmation of OvHV-2-induced MCF in species other than sheep can be routinely carried out in veterinary diagnostic laboratories with the detection of OvHV-2 DNA in blood or tissue samples by PCR, in combination with compatible histologic lesions.…”
mentioning
confidence: 99%